2022
DOI: 10.1111/all.15205
|View full text |Cite
|
Sign up to set email alerts
|

Comparing biologicals for severe chronic rhinosinusitis with nasal polyps: A network meta‐analysis

Abstract: To the Editor, We read with special interest the systematic review (SR) by Agache et al. 1 on the efficacy and safety of biologicals in patients with severe chronic rhinosinusitis with nasal polyposis (CRSwNP).Meta-analytical results were presented for the comparison between each biologic versus placebo, but indirect comparisons between different biologicals were not performed. Therefore, we aimed to complement this SR 1 with a network meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Across comorbidities and baseline eosinophil markers, type 2 biologics resulted in more CRSwNP patients with reduced polyp size and nasal obstruction than placebo 14,15 . Consistent results concerning action onset, magnitude, and persistence of biologics effects have been observed regardless of treatment duration 9,15 . Rapid and sustained improvement has been observed after biologics treatment irrespective of prior surgery, comorbid asthma or AR, treatment duration (20–24 weeks vs. ≥40 weeks), baseline mean IgE levels, and baseline mean eosinophil counts.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Across comorbidities and baseline eosinophil markers, type 2 biologics resulted in more CRSwNP patients with reduced polyp size and nasal obstruction than placebo 14,15 . Consistent results concerning action onset, magnitude, and persistence of biologics effects have been observed regardless of treatment duration 9,15 . Rapid and sustained improvement has been observed after biologics treatment irrespective of prior surgery, comorbid asthma or AR, treatment duration (20–24 weeks vs. ≥40 weeks), baseline mean IgE levels, and baseline mean eosinophil counts.…”
mentioning
confidence: 68%
“…These NMAs favored dupilumab as the most effective and safest biologic for CRSwNP. [6][7][8][9] Clinical benefits of continuing biologic treatment were sustained from 24 weeks to the end of follow-up. 10 Besides positive results from randomized controlled trials (RCTs), IL-4Rαtargeted therapy was more effective than anti-IL-5, anti-IL-5Rα, and anti-IgE biologics in a real-life retrospective analysis of patients with aspirin-exacerbated respiratory disease.…”
Section: E D I T O R I a L Knowledge Gaps In Using Type 2 Biologics F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, anti-IgE treatment has been approved in many countries as add-on therapy with intranasal corticosteroids for the treatment of adults with severe CRSwNP for whom therapy with intranasal corticosteroids does not provide adequate disease control. Noticeably, although Omalizumab is useful in the treatment of CRSwNP, a recent network meta-analysis and systematic review showed that anti-IgE antibodies are less effective than anti-IL-4 receptor antibodies ( 113 , 114 )…”
Section: The Function Of Ige and Anti-ige Treatment In Npsmentioning
confidence: 99%
“…Nowadays, anti-IgE treatment has been approved in many countries as add-on therapy with intranasal corticosteroids for the treatment of adults with severe CRSwNP for whom therapy with intranasal corticosteroids does not provide adequate disease control. Noticeably, although Omalizumab is useful in the treatment of CRSwNP, a recent network metaanalysis and systematic review showed that anti-IgE antibodies are less effective than anti-IL-4 receptor antibodies (113,114)…”
Section: Anti-ige Treatment In Npsmentioning
confidence: 99%